Stk10 Deficiency in Mice Promotes Tumor Growth by Dysregulating the Tumor Microenvironment - Jin-Xia Ma; Dan-Dan Xu; Shun-Yuan Lu; Qian-Lan Wang; Lu Zhang; Rui Guo; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; et al. (Biology, 2022)
Serine-threonine kinase 10 (STK10) is a member of the STE20/p21-activated kinase (PAK) family and is predominantly expressed in immune organs. Our previous reports suggested that STK10 participates in the growth and metastasis of prostate cancer via in vitro and in vivo data. However, the correlation between STK10 and the tumor microenvironment (TME) remains unclear. In this study, we assessed the relationship between STK10 and the immune cells in the tumor microenvironment of prostate cancer through bioinformatic analysis, and investigated the role of Stk10 in tumor growth using an Stk10 knockout mouse model. The results showed that STK10 is significantly associated with the tumor-infiltrating immune cells including lymphocytes, neutrophils, macrophages and dendritic cells. The target deletion of host Stk10 results in increased tumor growth, due to decreased activated/effector cytotoxic T lymphocytes (CTLs) and increased vessel density in the TME. In conclusion, we demonstrate that host Stk10 is involved in the host anti-tumor response by modulating the activated tumor-infiltrated CTLs and angiogenesis.